2004
DOI: 10.1111/j.1469-0691.2004.00961.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of sulesomab in the diagnosis of brucellar spondylitis

Abstract: Twenty-two patients with suspected brucellar spondylitis were investigated to evaluate the possible diagnostic role of Sulesomab, a (99m)Tc-antigranulocyte antibody Fab' fragment. Sensitivity and specificity were compared with those of magnetic resonance imaging (MRI). Skeletal involvement was detected by MRI in 11 cases, while leukoscintigraphy indicated normal vertebral uptake in seven of these patients, increased uptake in two patients, and decreased uptake in two patients. Leukoscintigraphy of the 11 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…In addition Gratz et al [7,8] reported an overall sensitivity and specificity of 76% and 84%, respectively, of Leukoscan scintigraphy for the diagnosis of infections involving bone, arthroplastic joint, or other tissues in 138 patients. Similar results were achieved by Cascio et al [30] in patients affected by brucellar spondylitis; the low sensitivity (27.2%) of Leukoscan in these patients was correlated with the chronic phase of the disease.…”
Section: Discussionsupporting
confidence: 87%
“…In addition Gratz et al [7,8] reported an overall sensitivity and specificity of 76% and 84%, respectively, of Leukoscan scintigraphy for the diagnosis of infections involving bone, arthroplastic joint, or other tissues in 138 patients. Similar results were achieved by Cascio et al [30] in patients affected by brucellar spondylitis; the low sensitivity (27.2%) of Leukoscan in these patients was correlated with the chronic phase of the disease.…”
Section: Discussionsupporting
confidence: 87%
“…Thoracolumbar spinal tuberculosis involving the vertebral body and more for osteolytic destruction, destruction of lesion or most often involving a vertebral destruction sequestrum see multiple irregularities in the kitchen, often involving the destruction of the vertebral pedicle rear, adjacent vertebral density generally reduced, local tissue reactions were; intervertebral disc damage, uneven density, there are "stars" like dead bone residue scattered in which the adjacent vertebral endplates irregular bone destruction or disappearance, most accompanied by paraspinal abscess formation, and calcification within the common abscess, abscess often exceed the length of the vertebral lesion formation flow injection abscess, abscess edge signal enhancement [24,25]; tuberculosis of the spine is the most reliable MRI features "jump lesion" and thin and smooth abscess wall and enhanced well-defined paraspinal abnormal signal (Figure 17) [26,27]. The Brucella spondylitis and more involved in the lower lumbar vertebral segments and 1 -2 [2,17], which is characterized by thick, irregular enhanced MRI abscess wall and ill-defined paraspinal abnormal signal, T1WI showed low signal, T2WI high signal to bone destruction evident when, T2WI high signal on fat suppression such as vertebrae, discs, accessories and intraspinal showed heterogeneous high signal (Figure 18) [2,3,[28][29][30][31].…”
Section: Manifestation Of Ct: Destructions Of the Interverbebral DImentioning
confidence: 99%